2014
DOI: 10.1039/c4mt00068d
|View full text |Cite
|
Sign up to set email alerts
|

Altered desferrioxamine-mediated iron utilization is a common trait of bald mutants of Streptomyces coelicolor

Abstract: Streptomyces coelicolor is an important model organism for developmental studies of filamentous GCrich actinobacteria. The genetic characterization of mutants of S. coelicolor blocked at the vegetative mycelium stage, the so-called bald (bld) mutants that are unable to erect spore-forming aerial hyphae, has opened the way to discovering the molecular basis of development in actinomycetes. Desferrioxamine (DFO) production and import of ferrioxamines (FO; iron-complexed DFO) are key to triggering morphogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
(85 reference statements)
3
41
0
Order By: Relevance
“…Transcript levels associated with genes in the desferrioxamine biosynthetic cluster ( sven_2568 and sven_2470/desA ) were higher in the double transporter mutant compared to wild type ( Fig. 5C ), consistent with what has been observed previously for bldK mutants in S. coelicolor (21). In contrast, genes in the other four siderophore-encoding biosynthetic clusters were unaltered in wild type and transporter mutant strains ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Transcript levels associated with genes in the desferrioxamine biosynthetic cluster ( sven_2568 and sven_2470/desA ) were higher in the double transporter mutant compared to wild type ( Fig. 5C ), consistent with what has been observed previously for bldK mutants in S. coelicolor (21). In contrast, genes in the other four siderophore-encoding biosynthetic clusters were unaltered in wild type and transporter mutant strains ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…The closest characterized homologues to these genes in the model S. coelicolor system were in the bldK locus ( sco5112-16 ). Recent work has suggested that BldK transporters function in ferrioxamine siderophore uptake (21). Increased expression for these two bldK- like transporter gene clusters in S. venezuelae implied that exploring cultures may adapt to alkaline, low-iron environments by coupling increased desferrioxamine production with enhanced ferrioxamine uptake.…”
Section: Resultsmentioning
confidence: 99%
“…'Das' stands for Defect in aerial hyphae and spore formation which refers to the impaired sporulation phenotype exhibited by the dasR null mutants of Streptomyces griseus [7] and Streptomyces coelicolor [2]. The observed developmental defect of dasR mutants fits with a regulon that extends well beyond GlcNAc and chitin utilization genes [8,9], such as gene clusters involved in the production of antibiotics prodiginines and actinorhodin [10] and the desferrioxamine siderophores [11] which are essential for proper sporulation of S. coelicolor [12,13]. The identification of the DasR regulon and the functional characterization of the genes it controls allows the description of the very first complete signalling cascade from extracellular signal transport to the control of secondary metabolite production in the industrially important Streptomyces genus [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, next to the role of iron as vital element for growth [38,39], morphogenesis and metabolite production [12,39,40], our work reveals an unprecedented complexity of natural product biosynthetic pathways where this element is also an environmental trigger able to change the pattern of natural compounds produced by a single BGC. By challenging the concept that one BGC should produce a single family of molecules, our results also highlight the difficulty to estimate the metabolic potential of an organism based on the genomic information alone.…”
Section: Figure 7 Proposed Pathway For Bagremycin a And Ferroverdin mentioning
confidence: 94%